2012
DOI: 10.1007/s11356-012-1367-1
|View full text |Cite
|
Sign up to set email alerts
|

Feral swine disturbance at important archaeological sites

Abstract: Feral swine are well known as environmentally destructive invasive animals in many areas around the world, where they degrade native habitats, harm rare plant and animal species, damage agricultural interests, and spread disease. We provide the first quantification of their potential as agents of disturbance at archaeological sites. Our study was conducted in south-central Florida at Avon Park Air Force Range, a base comprising over 40,000 ha and containing many archaeological sites. To determine the identifia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…We were particularly interested in identifying those sites most susceptible to swine disturbance based on artifact depth. Swine are known to root as deep as 1 m18 and easily root to 20 cm in depth121920 and their rooting has been documented in the literature as deep as 45 cm in Florida21. Among the 293 sites we surveyed, 261 (90%) were known to have artifacts within 20 cm of the surface and 247 (85%) were known to have artifacts within 10 cm of the surface (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We were particularly interested in identifying those sites most susceptible to swine disturbance based on artifact depth. Swine are known to root as deep as 1 m18 and easily root to 20 cm in depth121920 and their rooting has been documented in the literature as deep as 45 cm in Florida21. Among the 293 sites we surveyed, 261 (90%) were known to have artifacts within 20 cm of the surface and 247 (85%) were known to have artifacts within 10 cm of the surface (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because swine rooting commonly exceeds 20 cm in depth (e.g.refs 12, 19, 20 and 22) and 85% of our surveyed archaeological sites had been identified as having artifacts within 10 cm of the surface, and 90% had artifacts within 20 cm of the surface, the 42% rooting prevalence across the base’s archaeological sites revealed that a substantial percentage of sites were at risk for direct swine damage to artifacts, in addition to disturbance of their artifact stratigraphy and provenience. Although feral swine are capable of rooting to a meter in depth (e.g.ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feral swine have experienced signi cant range expansion over the past 30 years, in part because a subset of the human population wants to hunt them closer to home (Spencer et al 2005;Acevedo et al 2006;Saito et al 2012;Bevins et al 2014). This expansion has increased con icts with agriculture and humans, triggering several assessments of the costs and bene ts of feral swine in different locations (e.g., Higginbotham et al 2008;Campbell and Long 2009;Siemann et al 2009;Ober et al 2011;Engeman et al 2012;Mengak 2012;Campbell et al 2013;Bevins et al 2014). In addition, there has been considerable research on the increasing management con icts stemming from feral swine expansion (e.g., Weeks and Packard 2009;Honda and Kawauchi 2011;Koichi et al 2013;Warner and Kinslow 2013).…”
Section: Feral Swine: a Notorious Vismentioning
confidence: 99%